Regulatory and geopolitical challenges of Japonese Intelligence Services - López-Aranguren, José-Luis (Derecom. Derecho de la Comunicación y de Nuevas Tecnologías, 2023)
Japan faces several security challenges caused by four key factors. The first is the prohibition on maintaining an army and declaring war, as outlined in Article 9 of Japonese Constitution. The second is the nuclear threat arisen by North Korea. The third is the increasing tensions resulting from the expansion of Chinese influence. The fourth and final factor is Japan’s relationship with the United States, which is governed by the 1960 Treaty of Mutual Cooperation and Security. Given the importance of these issues to Japan’s national security, the country’s intelligence services must work to prevent and respond to both external and internal threats effectively. However, the efficiency of these services has been hampered by several factors, including the conflicting models of the centralized American CIA and decentralized British MI5 and MI6, as well as the bureaucracy of Japan’s public administration. This has highlighted the need for reform of Japan’s intelligence services. In this paper we go through the legal, historical and geopolitical context of the country’s intelligence services, the threats they have dealt with, and, finally, we will offer a proposal for reform that can help to cope with current and future challenges.